Appropriated Bodies: Trauma, Biopower and the Posthuman in Octavia Butler’s “Bloodchild” and James Tiptree, Jr.’s “The Girl Who Was Plugged In” - Ferrández San Miguel, María (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2018)
This article approaches science fiction using the strategically powerful perspectives of Trauma Studies and the posthuman in conjunction with Foucault’s notion of biopower, paying special attention to the deep investment of these discourses in notions of embodiment and agency. In order to do so, I will consider Octavia Butler’s 1984 short story “Bloodchild” (Hugo and Nebula Awards) and James Tiptree, Jr. (Alice Sheldon)’s 1973 novella “The Girl Who Was Plugged In” (Hugo Award). Both stories explore dystopian futures—in their focus on coercive extraterrestrials and life on an inhospitable planet, on the one hand, and on oppressive consumer culture and corporate technoscience, on the other—and point back to our posthuman present through metaphoric characters that illustrate and invite comment upon the articulation of power and the construction of the embodied posthuman. The main issue at play in the two stories, I will contend, is the identification of biopower with the traumatic appropriation of the human body and the articulation of posthuman forms of resistance to it. Keywords: trauma; the posthuman; biopower; science fiction; James Tiptree, Jr.; Octavia Butler